THE SPECIFITY OF THE CRIMINAL ACTS OF ROBBERY IN THE PRACTICE OF THE POLICE ADMINISTRATION OF SOMBOR - Dmitrašinović, Saša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
Summary: Robbery is a complex criminal offense in the field of property crime with elements of violence, prescribed in the Republic of Serbia by Article 206 of the Criminal Code. The dynamics and frequency of the manifestations of this crime in everyday life, as well as the extent and intensity of the consequences, contribute to the constant topicality of the research and the need for a more comprehensive understanding of this phenomenon. Therefore, the focus of our research is directed towards the cognition of the situation and tendencies in the area of ​​opposing the acts of robbery. Specifically, the paper dominates the appearance of this crime and other phenomenological features in the criminal practice of the Sombor Police Department. By looking at the complex phenomenology of robbery, the crucial elements of a strategy for combating property crime with elements of violence are analyzed, as well as the key issue of selecting concrete measures and actions in police work. Keywords: robbery, property offenses with elements of physical violence, phenomenology, modus operandi, PU Sombor.